Post-Colonial Identities: multi-lingual, multi-ethnic and multi-cultural - Figueiredo, Rosa Branca (2016)
Taking Soyinka’s latest writings onto account it is easy to see that contemporary multi-ethnic, multi-lingual and multi-cultural African nation-state has become a failure. Most governments have been unstable owing to ethnic competitions for political power and economic advantages. Laws have been outlawed because of corruption and there is no learning to be had in the educational institutions whose infrastructure has decayed. Taking Nigeria as an example because it is Soyinka’s home country, we understand that there the basis for the struggle against British imperialism was not one Nigerian nation. Rather, the ‘struggle’ was waged on the basis of liberal ideals of selfdetermination, freedom of organization and the scrambled pan- African ideals of anti-racism, and anti-imperialism. The succession of dictatorships – civilian or military, malevolent or benevolent, competent or incompetent made it impossible to discuss the concepts which should underlie the new nation. It is only recently through national conferences taking place in different parts of the continent that serious thought is now being given to the idea of the nation in its multi-ethnicity, multi-lingualism and multiculturalism. What we intend to show in this paper is how Soyinka’s plays assert that for Africa to reform and renew itself, it must borrow from the experiences of the rest of the world.